2019
DOI: 10.1002/ece3.4848
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic plasticity closely linked to climate at origin and resulting in increased mortality under warming and frost stress in a common grass

Abstract: Phenotypic plasticity is important for species responses to global change and species coexistence. Phenotypic plasticity differs among species and traits and changes across environments. Here, we investigated phenotypic plasticity of the widespread grass Arrhenatherum elatius in response to winter warming and frost stress by comparing phenotypic plasticity of 11 geographically and environmentally distinct populations of this species to phenotypic plasticity of populations of different species originating from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 63 publications
4
28
0
Order By: Relevance
“…However, it is important to note that high plasticity is not inherently positive for local population persistence (cf. Kreyling et al., 2019), as it implies large differences in survival with changing environmental parameters, that is, limited survival under certain conditions.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is important to note that high plasticity is not inherently positive for local population persistence (cf. Kreyling et al., 2019), as it implies large differences in survival with changing environmental parameters, that is, limited survival under certain conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Despite this, we find it important to discuss phenotypic plasticity. Both recent and earlier studies have shown that the high phenotypic plasticity of plants should not be universally seen as a positive attribute [43,45,110,111]. The plasticity cost might not be pronounced under normal conditions, but when plants are exposed to a highly stressful environment, the plasticity cost might outweigh the fitness gain [112,113].…”
Section: Phenotypic Plasticitymentioning
confidence: 95%
“…This is generally seen as favourable under stress conditions because it enables plants to react to fluctuations in the environment [41,42]. However, several studies have reported a potential trade-off between phenotypic plasticity and individual fitness [43], suggesting reduced performance with increasing plasticity [38,44,45]. Therefore, it is crucial to assess the ability for stomatal and leaf morphological traits to react plastically to their environment and to test the connection between their phenotypic plasticity and plant fitness and performance.…”
Section: Introductionmentioning
confidence: 99%
“…The high PPI value in the Lingga-1 population may be caused by more variable environmental conditions compared to other populations. According to Kreyling et al (2019), phenotypic plasticity is not related to neutral genetic diversity, but it is closely related to environmental conditions, mainly the climate of the population origin. The population that has a low PPI value tends to be phenotypically uniform if their genetic material is exposed to fluctuating environmental conditions.…”
Section: Phenotypic Plasticity Indexmentioning
confidence: 99%